Unlimited Capitalism and the Politics of the Common: Review of Pierre Dardot and Christian Laval’s Commun: essai sur la revolution au XXIe siècle - Narita, Felipe Ziotti (Praktyka Teoretyczna, 2018)
A review of Pierre Dardot and Christian Laval’s book Commun: essai sur la révolution au XXIe siècle. Following a manuscript published by the author at Pós Ciências Sociais (a peer-reviewed journal on the social sciences of Federal University of Maranhão – Brazil), in this text the author discusses Dardot and Laval’s approach to the problem of the common in light of both their theoretical path and the contemporary political impasses of neoliberal capitalism. In this sense, three main axes are articulated in this text: the institution of the common, neoliberal rationality and the problem of governmentality.